1997
DOI: 10.1021/om960783q
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of the [2+2]- and [2+3]-Cycloaddition Mechanisms for the Osmium-Catalyzed Dihydroxylation of Olefins

Abstract: The postulated intermediates in the base-free and base-assisted addition of OsO4 to olefins have been optimized using density functional theory (DFT). Ammonia was chosen as the base and ethylene as the olefin. The corresponding transition states have been characterized fully. Further, the activation barriers have been computed at the nonlocal level, and special attention has been given to the two different mechanistic hypothesis proposed for this reaction. In particular, the hypothesis by Sharpless of a [2+2]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(56 citation statements)
references
References 59 publications
3
51
0
2
Order By: Relevance
“…One intriguing possibility is the use of cis-metal dioxo compounds that could react with MÀR s bonds in a potentially facile addition reaction via a (3+2)-type transition state (TS, see Figure 2). Related mechanisms are well known for the cis-dihydroxylation of alkenes by OsO 4 [5] and the oxidation of the s bonds of hydrogen, [6] silanes, [7] and alkanes. [8] Herein we report the quantitative and instantaneous oxyfunctionalization of MTO to methanol by reaction with OsO 4 in aqueous basic media at room temperature [Eq.…”
mentioning
confidence: 97%
“…One intriguing possibility is the use of cis-metal dioxo compounds that could react with MÀR s bonds in a potentially facile addition reaction via a (3+2)-type transition state (TS, see Figure 2). Related mechanisms are well known for the cis-dihydroxylation of alkenes by OsO 4 [5] and the oxidation of the s bonds of hydrogen, [6] silanes, [7] and alkanes. [8] Herein we report the quantitative and instantaneous oxyfunctionalization of MTO to methanol by reaction with OsO 4 in aqueous basic media at room temperature [Eq.…”
mentioning
confidence: 97%
“…The initial model (Figure 3.2a) for the transition state was based on a [2 þ 2] cycloaddition reaction model and, although NMR studies support this, there is now evidence and consensus that a [3 þ 2] model is followed [123][124][125][126][127][128][129][130]. Computational studies suggest that solvent can play a key role in account for the apparent reversal of reaction stereochemical outcome compared to that predicted by Sharplesss original mnemonic (Figure 3.2a).…”
Section: Mechanismmentioning
confidence: 99%
“…The calculations indicated that formation of a metallaoxetane is possible and that its geometry fit with empirical (mnemonic) models used to explain the stereoselectivity in these reactions . However, DFT calculations performed a few years later by different groups on osmium models concluded that the [3+2] pathway is strongly favored …”
Section: Historical Perspective On Qm Studies Of Asymmetric Reactionsmentioning
confidence: 99%